Proposed Model For Teleradiological System For Medical Telediagnosis Process - Rafida Hameed Ahmad (College of Education for Pure Sciences, 2009)
Abstract The need and importance of radiographs in the diagnostic process makes the Telediagnosis system depends on the Teleradiology application and its services as important sources for diagnostic information. This article discusses this need that creates faster diagnosis. A proposed teleradiological prototype system was described, which can be used in the open hospitals on the Internet. The scenario of such system that explains the role of radiologist in the diagnosis process was explained. The equipments needed for the information of this system, methods of transmission, and some of current teleradiology systems in use were mentioned.